Characterization and mapping of a putative laccase-like multicopper oxidase gene in the barley (Hordeum vulgare L.) - Tomková, Lenka; Kučera, Ladislav; Vaculová, Kateřina; Milotová, Jarmila (Plant science, 2012)
Laccases constitute a multi-gene family of multi-copper glycoproteins. The barley laccase-like multicopper oxidase (LMCO) gene structure, the DNA sequence polymorphism and putative protein have not yet been described. As part of the study of LMCO in cereals, we have characterized the genomic structure of the putative LMCO gene HvLac1 from the barley variety 'Morex' and mapped HvLac1 on chromosome 4H. The genomic sequence of the HvLac1 gene is 2646 bp long and covers 100% of the coding region. It contains four exons and three introns. In this study, we have described the HvLac1 gene nucleotide polymorphisms (In/Del) in 134 barley varieties. Initial characterization of the barley and rice LMCO and the phylogeny analysis indicate that a monocot LMCO family is composed of five members. There are two high pI isoforms of putative HvLac1 protein derived from two in frame translation start codons with 602aa or 592aa residues. Isoforms differ in their predicted subcellular localization and both isoforms are characterized on C-terminus by the presence of the KDEL-like motif, which contributes to the accumulation of soluble proteins in the endoplasmic reticulum. Our results suggest that this unique feature of HvLac1 could be important for their role in physiological processes.
Keywords: ječmen (rod); Base Sequence; DNA, Plant; mapování chromozomů; sekvence aminokyselin; Chromosome Mapping; Plant Proteins; lakasa; Molecular Sequence Data; Amino Acid Sequence; rostlinné proteiny; Phylogeny; molekulární sekvence - údaje; Protein Conformation; polymorfismus genetický; DNA rostlinná; sekvence nukleotidů; Sequence Analysis, DNA; konformace proteinů; Laccase; Hordeum; sekvenční analýza DNA; fylogeneze; Polymorphism, Genetic